Faktor yang Mempengaruhi Lost To Follow-Up Pasien HIV-AIDS Dengan Terapi ARV Pada Kelompok LSL - Aulia, Ulfa; Andriani, Ni Ketut; Irwan, Irwan (Preventif : Jurnal Kesehatan Masyarakat, 2024)
Based on the situation report on the development of HIV-AIDS & PIMS, HIV-AIDS first appeared in Indonesia in 1987 and spread to 463,000 cities and districts (90.07%). HIV-AIDS cases continue to increase every year, reaching 349,882 HIV cases and 117,064 AIDS cases. However, not everyone who is HIV positive is diagnosed. According to the Indonesian Ministry of Health (2019), there were 244,142 HIV-AIDS sufferers who received ARV therapy (70% of the total), but only 115,750 people (33%) received regular treatment, and 55,508 people stopped their treatment. The aim is to analyze the factors that influence lost to follow-up ARV therapy in the MSM group. The research method is analytical observation with a case control approach. Population of HIV-AIDS patients who have lost to ARV follow-up and HIV-AIDS patients on active ARV therapy. The sample in this study was 66 patients using a cluster random sampling technique. Data analysis uses logistic regression test. Results: analysis for adherence to ARV therapy ρ-value 0.367 > α (0.05), family support ρ-value 0.049 < α (0.05), and perceived severity ρ-value 0.014 < α (0.05). The conclusion is that there is an influence between family support and perceived severity. Suggestions for patients to be more open about their health status.